Analysis of Standardization of Physics Laboratory Management at SMA Negeri 3 Jember to Improve the Quality of Student Learning - Nasabella, Nazwa; Ahmad Dzikri Fadholi Robbi; Arini Azrin Fakhira; Mayang Maharika; Febby Putri Wulandari; Lailatul Nuraini; Alex Harijanto (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The aim of this research is to evaluate the management standards of the physics laboratory at SMA Negeri 3 Jember and determine the factors that influence the quality of student learning. This research uses descriptive qualitative methods with data collection techniques through observation, interviews and documentation. The subjects of this research were school principals, physics teachers, and students in grades X, XI, and XII. The data obtained was then analyzed using the Miles and Huberman interactive analysis model. The results of this research indicate that the physics laboratory management standards at SMA Negeri 3 Jember have met national education standards. This can be seen from several aspects, such as planning, implementation, supervision, evaluation and development